DETERMINATION OF 120MM / 46A PREVENTIVE CARE INTERVALS FOR MINVET BOATS FOR INCREASING THE RELIABILITY OF THE SYSTEM - Sutrisno Sutrisno; Arief Saepullah; Setiawan Bernadi; Djoko Kriswanto (JOURNAL ASRO, 2018)
Most warships, especially corvette types, have a service life of more than twenty years. Intuitively it can be concluded that the components and equipment that have been installed are in the period of wear from the bathtub curve. This paper presents an alternative method in determining the optimum component maintenance intervals for weapons system equipment on ships that have entered wear (wear out). Optimum maintenance costs are determined by optimizing the component maintenance interval with objective functions to minimize the total cost of increasing reliability. The reliability of the system is achieved by increasing the reliability index of its constituent components. Weibull ++ is used to obtain parameters that are appropriate for each damage distribution, while Excel Solvers are used to calculating optimal maintenance intervals. In this writing, a case study will be carried out on the components of Bofors cannon laying gear TAK 120MM / 46A